Hydrodynamic coefficients and forces on multihulls in shallow water with constant or variable depth - Dabssi, Noureddine; Chagdali, Mohamed; Hémon, Alain (Transport, 2008)
Numerical and hydro dynamical procedures are developed to compute bidimensional hydrodynamic coefficients and forces on multihulls associated with harmonic oscillations in shallow water with constant or variable depth. The forces are composed of two parts and include the sum of incident and diffracted forces and hydrodynamic reaction. The latter one is used to determinate the hydrodynamic coefficients (added mass and damping). The numerical method used is the Boundary Element Method. We can compute flow around multihulls sections. An application to cylindrical, right triangular and rectangular hull forms is presented. First published online: 27 Oct 2010